Characterization of polysaccharides isolated from stem of Angelica dahurica (Mongolian Journal of Agricultural Sciences, 2014)
Such pectin (5.77±0.02)%, fiber (24±0.01)%, lignine (10.790.03)% have been founded in the medicinal herb called ‘Angelica’. The average molecule mass of pholysugar was determined by the methodology of chromatography of chromatography of gel-filtration of the (15500-400000). It has founded first time that the glucose thermal galactose has connected as 1,4 connection in connection with the monomer assortment of neutral pholysugar founded in monosaccharide. The rhamnose-terminal, xylose-terminal are connected by 1,3 connection in the circulation of macromolecule of polysaccharide. Pectin of substance derivative compound to extract. In polysaccharide has to establish etherify carboxyl group (7.47)% and methoxyl group (5.14)% and etherification degree (51.4)%. DOI: http://dx.doi.org/10.5564/mjas.v11i2.236 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.142-145